Posttraumatic Osteoarthritis Development and Progression in an Ovine Model of Partial Anterior Cruciate Ligament Transection and Effect of Repeated Intra-articular Methylprednisolone Acetate Injections on Early Disease. Issue 7 (June 2018) - Barton, Kristen I.; Heard, Bryan J.; Sevick, Johnathan L.; Martin, C. Ryan; Shekarforoush, S.M. Mehdi; Chung, May; Achari, Yamini; Frank, Cyril B.; Shrive, Nigel G.; Hart, David A.
Background: Partial anterior cruciate ligament (p-ACL) ruptures are a common injury of athletes. However, few preclinical models have investigated the natural history and treatment of p-ACL injuries. Purpose: To (1) demonstrate whether a controlled p-ACL injury model (anteromedial band transection) develops progressive gross morphological and histological posttraumatic osteoarthritis (PTOA)–like changes at 20 and 40 weeks after the injury and (2) investigate the efficacy of repeated (0, 5, 10, and 15 weeks) intra-articular injections of methylprednisolone acetate (MPA; 80 mg/mL) in the mitigation of potential PTOA-like changes after p-ACL transection. Study Design: Controlled laboratory study. Methods: Twenty-one 3- to 5-year-old female Suffolk-cross sheep were allocated to 4 groups: (1) nonoperative controls (n = 5), (2) 20 weeks after p-ACL transection (n = 5), (3) 40 weeks after p-ACL transection (n = 6), and (4) 20 weeks after p-ACL transection + MPA (n = 5). Gross morphological grading and histological analyses were conducted. mRNA expression levels for inflammatory, degradative, and structural molecules were assessed. Results: p-ACL transection led to significantly more combined gross damage ( P = .008) and significant aggregate histological damage ( P = .009) at 40 weeks after p-ACL transection than the nonoperative controls, and damage was progressive over time. Macroscopically, MPA appeared to slightly mitigate gross damage at 20 weeks after p-ACL transection in some animals. However, microscopic analysis revealed that repeated MPA injections after p-ACL transection led to significant loss in proteoglycan content compared with the nonoperative controls and 20 weeks after p-ACL transection ( P = .008 and P = .008, respectively). Conclusion: p-ACL transection led to significant gross and histological damage by 40 weeks, which was progressive over time. Multiple repeated MPA injections were not appropriate to mitigate injury-related damage in a p-ACL transection ovine model as significant proteoglycan loss was observed in MPA-treated knees. Clinical Relevance: A p-ACL injury leads to slow and progressive PTOA-like joint damage, and multiple repeated injections of glucocorticoids may be detrimental to the knee joint in the long term.